Distribution of Malassezia species in patients with psoriasis – quality assessment - Rup, Elżbieta; Skóra, Magdalena; Krzyściak, Paweł; B. Macura, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Introduction : The fungi Malassezia are a constituent of the skin microbiota in humans and some animals. The fungi may cause skin diseases or even organ and/or generalized infections in the presence of appropriate predisposing factors. Aim : To evaluate the occurrence of Malassezia fungi on the skin in patients with psoriasis and to search for a relationship between the occurrence of Malassezia and the severity of skin lesions as well as the age and sex of the patients. Material and methods: The materials comprised smears sampled from four sites: scalp, face, chest and back. Malassezia spp. were isolated in cultures on modified Dixon medium and identified on the basis of morphological and biochemical features. Results: Malassezia spp. were isolated in 57.7% of the patients. The fungi were most prevalent on the chest (37.3%) and least on the scalp (9.8%). The prevalence on the back and face was comparable, 27.5% and 25.5% respectively. Conclusions : No statistically significant differences were found between Malassezia prevalence in males vs. females. No relationship with the patients’ age was found. Higher values of the psoriasis area and severity index (PASI), and of the body surface area (BSA) were found in the patients in whom Malassezia spp. were isolated.